Dividend Policy During Covid-19 - Suhariyanti, Tri (Jurnal Kompetitif Bisnis, 2020)
In dealing with the effects of the Covid-19 pandemic, which makes the company’s stock price go down, the company needs a strategy to survive in the capital market. One of the strategies is implementing a high dividend distribution policy. This policy is complied with signalling theory which argues that the high dividends give a signal that the company has good prospects in the future. This aims to attract investors to buy back the company’s shares, which will have an impact on increasing the company’s stock price. However, there are also companies that cancel the distribute of dividends to support the company’s financial stability. This article aims to describe the theory that underlies the policy of high dividend distribution adopted by companies to deal with the effects of the Covid-19 pandemic.